Hibridasi dan Habitus Pendidikan Islam Tradisional Langgar dalam Masyarakat Madura di Jember, Jawa Timur - Sibilana, Annas Ribab (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
Traditional education is one of the treasures of traditional Islamic education in the archipelago. Langgar was one of the centers of traditional Islamic education in Indonesia before the development of pesantren. This study seeks to present traditional education in the context of Madurese society in Jember. This research was conducted in Langgar Nurul Huda in Kemuning Lor village, Panti District. The research method used is ethnographic, with in-depth interviews with kiai langgar, santri and santri parents. The results showed that the Madurese ethnic community in Jember showed a hybrid society through various cultural expressions in language, symbols, and art. The learning model used in Langgar Nurul Huda seems to provide "cultural communication" that this Langgar is a Langgar that has a Madurean identity; this can be seen from Langgar's various activities. Langgar's traditional education model in Langgar Nurul Huda shows Madurese's identity through language expressions and cultural symbols. The categorization of ethnicity in this study is understood as the habitus of Madurese people formed through the representation of Langgar, the expression of identity "kemaduraan" (Madurese Identity) reflected in the identification of models and learning patterns. The learning style is Pal-apalan, (memorize) Ca'beca'an. (reading), and Ngajhi (recite). It shows how Madurese people in Jember identify their ethnic identity through the distinctive Langgar traditional learning model.